Performance Of Village Equipment In Management Of Village Funds For 2021 Budget In Sungai Nilau Village Sungai Manau District Merangin District Jambi Province - Candra Andika; Hadi Prabowo; Prio Teguh (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2023)
The focus of this research is to look at the Performance of Village Apparatus in the management of Village Funds in Sungai Nilau Village, Sungai Manau District, Merangin Regency, and determine strategies that should be carried out to Improve Village Apparatus Performance in Village Fund Management in Sungai Nilau Village, Sungai Manau District. The research uses theory by Agus Dwiyanto related to performance indicators, then conducts a SWOT analysis and Osborne and Plastric litmus tests to determine strategies. This research uses qualitative methods with a descriptive approach. In collecting data, researchers conducted observations, interviews and collected documents about the performance of Village Apparatus in Village Fund Management in Sungai Nilau Village. The results showed that the Village Apparatus Performance in Village Fund Management in Sungai Nilau Village was not optimal. There is still a lack of productivity, service quality, and responsibility for the resulting activities, due to the lack of competence and expertise of village officials in managing the Village Fund. Then the availability of limited human resources, limited financial resources and limited infrastructure and equipment.